Fate of pharmaceutically active compounds in a pilot-scale A2O integrated fixed-film activated sludge (IFAS) process treating municipal wastewater. Issue 4 (August 2021) - Gallardo-Altamirano, M.J.; Maza-Márquez, P.; Pérez, S.; Rodelas, B.; Pozo, C.; Osorio, F.
Abstract: The goal of this research was to study the operation of an integrated fixed-film activated sludge system (IFAS), in anaerobic/anoxic/aerobic (A2O) configuration for the elimination of emerging pollutants, in particular of 27 pharmaceutical active compounds (PhACs) (eight anti-inflammatory and/or analgesic pharmaceuticals (AIAPs), six antibiotics, four b-blockers, two antihypertensives/diuretics, three lipid regulators-bezafibrate and four psychiatric medications). Different operational conditions were analyzed in the biological reactor, controlling at all times both the amount of suspended and fixed biomass present. The A2O-IFAS system has obtained similar or higher removal efficiency (RE) in the elimination of organic matter, and especially of nutrients, nitrogen (N) and phosphorous (P), with respect to the conventional A2O system, working however with very low values of the sludge retention time (SRT) (4.0 days) and mix liquid suspended solid (MLSS) in the reactor (1822 mg L-1). In general, conventional activated sludge (CAS) and IFAS processes show the importance of operating at high SRT and MLSS concentration, that give low food/microorganisms (F/M) ratio, to increase the RE of several PhACs. However, the A 2 O-IFAS system, operating with low mixed liquor SRT and MLSS has achieved similar or better RE of PhACs, obtaining the highest average REs values (>80%) for fenofibrate, acetaminophen, ibuprofen, naproxen, clarithromycin and atenolol. According to the results obtained, due to the affordable cost and well-demonstrated performance, IFAS systems become one of the most promising technology for conventional wastewater treatment plants (WWTP) upgrading. Graphical Abstract: ga1 Highlights: Removal efficiencies (REs) of 27 PhACs were assessed in a pilot-scale A 2 O-IFAS. The REs of PhACs were compared between the A 2 O system and the A 2 O-IFAS system. The A 2 O-IFAS system achieved higher REs of nutrients and PhACs compared to the A 2 O system. Several operational/performance parameters and PhACs REs were correlated.